2009
DOI: 10.1111/j.1369-1600.2009.00153.x
|View full text |Cite
|
Sign up to set email alerts
|

PRECLINICAL STUDY: Amphetamine‐ and nicotine‐induced cross‐sensitization in adolescent rats persists until adulthood

Abstract: Nicotine and psychostimulants are often abused in combination and drug abuse often begins during adolescence and can have long-term consequences. Behavioral sensitization has been suggested as an animal model of neuroplasticity implicated in the development of drug addiction. We evaluated whether the pretreatment with nicotine (0.4 mg/kg; s.c.) or amphetamine (5.0 mg/kg; i.p.) in adolescent rats [from postnatal day (P) 28 to P34] could induce cross-sensitization to nicotine and amphetamine when animals were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 35 publications
3
25
0
Order By: Relevance
“…For example, it has been shown, under the same conditions, that adolescent rats may self-administer higher doses of amphetamine than adults (Mathews et al 2009;Shahbazi et al 2008). Moreover, in adult rats acute low doses of amphetamine significantly increase locomotor activity, but this effect is not observed in adolescent rats suggesting that the latter are less sensitive to psychostimulant drugs (Bolanos et al 1998;Mathews and McCormick 2007;Santos et al 2009;Schramm-Sapyta et al 2009). …”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, it has been shown, under the same conditions, that adolescent rats may self-administer higher doses of amphetamine than adults (Mathews et al 2009;Shahbazi et al 2008). Moreover, in adult rats acute low doses of amphetamine significantly increase locomotor activity, but this effect is not observed in adolescent rats suggesting that the latter are less sensitive to psychostimulant drugs (Bolanos et al 1998;Mathews and McCormick 2007;Santos et al 2009;Schramm-Sapyta et al 2009). …”
Section: Introductionmentioning
confidence: 91%
“…This phenomenon is termed behavioral sensitization, which is suggested to reflect neuroadaptive processes associated with drug addiction (Covington and Miczek 2001;Robinson and Berridge 1993). Taking this into account, studies have shown that amphetamine induces behavioral sensitization in both adult and adolescent rats (Mendez et al 2009;Santos et al 2009;Tirelli et al 2003). The mesolimbic dopamine system is critically involved in the locomotor activation produced by psychostimulants (Giorgi et al 2005b).…”
Section: Introductionmentioning
confidence: 94%
“…For example, it has been demonstrated that repeated exposure to nicotine sensitizes the locomotor response to cocaine and amphetamine in periadolescent rats (24,25). It has also been demonstrated that long-term amphetamine (6,26) or caffeine (26) induces behavioral sensitization to nicotine. However, at present the degree to which repeated MPD treatment during adolescence subsequently augments the locomotor response to nicotine is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to psychostimulants during adolescence can have long-term consequences because early drug exposure may cause enduring adaptations, which render the organism more susceptible to drug abuse and relapse later in life (5,6).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation